2019
DOI: 10.2147/cwcmr.s157211
|View full text |Cite
|
Sign up to set email alerts
|

<p>Fish skin acellular dermal matrix: potential in the treatment of chronic wounds</p>

Abstract: The role of cellular and tissue-based therapies (CTPs) in the treatment of chronic wounds continues to grow. However, the utility of these is only partially investigated and very few head-to-head studies exist. In general, the ideal CTP would provide a structural matrix which would allow for dermal and epidermal regeneration with a single application. At present, this Holy Grail is very far from where we are. However, new CTPs continue to be designed with the goal of wound closure in mind. Acellular fish skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…There was a significant ( P < 0.0001 ) reduction in the microbial contamination of the tilapia skin dressed wounds achieving complete inhibition of microorganism growth on 21 days post-wound induction. This may be attributed to the fact that fish skin has antimicrobial properties, therefore, can combat local infection [ 25 28 ]. Consistently, the wound area dressed with fish skin was infiltrated with inflammatory cells (neutrophils and macrophages) as early as day 7 post-wounding.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant ( P < 0.0001 ) reduction in the microbial contamination of the tilapia skin dressed wounds achieving complete inhibition of microorganism growth on 21 days post-wound induction. This may be attributed to the fact that fish skin has antimicrobial properties, therefore, can combat local infection [ 25 28 ]. Consistently, the wound area dressed with fish skin was infiltrated with inflammatory cells (neutrophils and macrophages) as early as day 7 post-wounding.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, skin grafts from fish such as Atlantic cod have been proposed because viral and prion transmission risk is nonexistent. These tissues can be subjected to gentle processing that does not disrupt the structure or bioactive composition of the original ECM [29].…”
Section: Small Intestine Submucosamentioning
confidence: 99%
“…Additionally, fish skin heals faster than human skin without leaving scar tissue [54]. The histological analysis of human skin after a Kerecis™ graft demonstrated that the ADM is incorporated into the damaged area and infiltrated by autologous cells, is resistant to bacteria, and exhibits anti-inflammatory properties because of the omega-3 fatty acids [29,54].…”
Section: Animal-derived Admsmentioning
confidence: 99%
“…However, patients with severe burns may not receive adequate skin grafts and are at a greater risk of acquiring infections, including hepatitis B or C [ 3 ]. Besides, another traditional approach for chronic wound therapy is via fish skin acellular treatment [ 4 ]. This method is considered as one of the significant treatments due to its histological properties that promote cellular regulation and is rich with omega-3 fatty acids to supply to the local tissue [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%